Mechanisms for low-frequency variability of summer Arctic sea ice extent - Zhang, Rong (Proceedings of the National Academy of Sciences - PNAS, 2015)
Satellite observations reveal a substantial decline in September Arctic sea ice extent since 1979, which has played a leading role in the observed recent Arctic surface warming and has often been attributed, in large part, to the increase in greenhouse gases. However, the most rapid decline occurred during the recent global warming hiatus period. Previous studies are often focused on a single mechanism for changes and variations of summer Arctic sea ice extent, and many are based on short observational records. The key players for summer Arctic sea ice extent variability at multidecadal/centennial time scales and their contributions to the observed summer Arctic sea ice decline are not well understood. Here a multiple regression model is developed for the first time, to the author’s knowledge, to provide a framework to quantify the contributions of three key predictors (Atlantic/Pacific heat transport into the Arctic, and Arctic Dipole) to the internal low-frequency variability of Summer Arctic sea ice extent, using a 3,600-y-long control climate model simulation. The results suggest that changes in these key predictors could have contributed substantially to the observed summer Arctic sea ice decline. If the ocean heat transport into the Arctic were to weaken in the near future due to internal variability, there might be a hiatus in the decline of September Arctic sea ice. The modeling results also suggest that at multidecadal/centennial time scales, variations in the atmosphere heat transport across the Arctic Circle are forced by anticorrelated variations in the Atlantic heat transport into the Arctic. Significance The observed decline in summer Arctic sea ice has often been attributed, in large part, to the increase in greenhouse gases. However, the contributions from internal low-frequency variability in the climate system are not well understood. Here a multiple regression model is developed for the first time, to the author’s knowledge, to quantify the contributions of three key predictors on the internal low-frequency variability of summer Arctic sea ice extent. If the ocean heat transport into the Arctic were to weaken in the near future due to internal variability, there might be a hiatus in the decline of September Arctic sea ice, and a delay in attaining a summer ice-free Arctic. This plausible scenario with broad ecological and economic impacts should not be ignored.